2013
DOI: 10.1074/jbc.m112.420620
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cardiac Lipolysis in Mice Critically Depends on Comparative Gene Identification-58

Abstract: Background:The role of CGI-58 in muscle triacylglycerol catabolism is unknown. The presence of CGI-58 increases the lipolytic activity of adipose triglyceride lipase (ATGL). Results: Muscle-specific CGI-58 deficiency causes muscle steatosis and cardiac dysfunction despite elevated ATGL protein expression. Conclusion: Muscle lipolysis critically depends on both CGI-58 and ATGL. Significance: Muscle CGI-58 deficiency provokes severe cardiac steatosis and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 45 publications
(53 reference statements)
6
53
2
Order By: Relevance
“…Furthermore, the expression of PPAR ␣ (and ␤ / ␦ ) target genes involved in mitochondrial FAO was moderately but signifi cantly reduced, which could be a consequence of impaired lipolysis, as has been reported for mice lacking ATGL or CGI-58 specifi cally in muscle ( 15,16 ). The observation that CM-Fgf21 mice exhibit normal heart function suggests that in these animals mitochondrial FAO is more moderately affected as compared with the marked defect in mitochondrial FAO and cardiac function of ATGL-defi cient mice.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, the expression of PPAR ␣ (and ␤ / ␦ ) target genes involved in mitochondrial FAO was moderately but signifi cantly reduced, which could be a consequence of impaired lipolysis, as has been reported for mice lacking ATGL or CGI-58 specifi cally in muscle ( 15,16 ). The observation that CM-Fgf21 mice exhibit normal heart function suggests that in these animals mitochondrial FAO is more moderately affected as compared with the marked defect in mitochondrial FAO and cardiac function of ATGL-defi cient mice.…”
Section: Discussionsupporting
confidence: 55%
“…This assumption is further supported by the strong induction of FGF21 expression in differentiated H9C2 cardiomyotubes when treated with ER stress-activating agents including DTT, tunicamycin, and palmitate. Mice lacking the ATGL coactivator CGI-58 in CM (and skeletal muscle) ( 15 ) show a similar increase in cardiac FGF21 expression.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was also reported that LDs supply lipid ligands, FAs and their metabolites, for PPAR␣ activation through lipolysis (22,(36)(37)(38). In the hearts of diabetic Plin5 Ϫ/Ϫ mice, LDs were not detectable, and the intramyocardial FA levels were lower than those of diabetic WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, abnormal lipid metabolism, including aberrant lipid accumulation, is regarded as an important pathogenesis of diabetic cardiomyopathy. Efforts have been made to elucidate the link between lipid metabolism and heart performance using obese and diabetic mouse models as well as genetically modified mice (16)(17)(18)(19)(20)(21)(22)(23)(24). Previous studies focusing on abnormal lipid metabolism suggest two causes for major pathogenesis of diabetes-induced heart malfunction.…”
mentioning
confidence: 99%